A Backward Euler Method Based Thévenin Equivalent Integral Model for Full-bridge Modular Multi-level Converters. Issue 3 (7th February 2016) - Xu, Jianzhong; Zhao, Chengyong
Abstract: –The Thévenin equivalent electromagnetic transient model of the full-bridge modular multi-level converter adopts Dommel's Algorithm to discretize individual capacitor to maintain the identity of each switching level and achieves significant CPU time savings. This article presents an enhanced integral full-bridge modular multi-level converter model with built-in efficient sorting algorithms. Basically it achieves further speedup from the traditional equivalent algorithm by assuming the switch's "OFF" condition as an ideal open circuit, by using the A-stable backward Euler integration method instead of the trapezoidal rule to discretize the individual capacitor in each sub-module and by using the proposed efficient capacitor voltage sorting algorithm. Then the blocking implementation method and the way to simulate the open and short-circuit faults of the internal full-bridge modular multi-level converter devices are also provided to make the full-bridge modular multi-level converter model complete and effective. The validity and scalabilities of the presented model are demonstrated using closed-loop simulation of a back-to-back high-voltage DC system and open-loop simulations of full-bridge modular multi-level converters. The results obtained from both demonstrations have shown that the presented integral model is able to accurately simulate the typical behaviors of the full-bridge modular multi-level converter during normal operation and AC/DC network transients.